2021
DOI: 10.1080/19336918.2021.1909899
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinate-curcumin inhibits AngII-induced vascular smooth muscle cell phenotype switching by upregulating Daxx expression

Abstract: Phenotypic switching is the main cause of the abnormal proliferation and migration of vascular smooth muscle cells (VSMCs). We previously showed that Daxx exerted negative regulatory effect on AngII-induced VSMC proliferation and migration. However, the function of Daxx in VSMC phenotype switching remained unknown. Nicotinate-curcumin (NC) is an esterification derivative of niacin and curcumin that can prevent the formation of atherosclerosis. We found that NC significantly decreased AngII-induced VSMC phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Indeed, a study by Li et al (2017) has shown that curcumin attenuates Ang II-induced expressions of inflammatory factors and oxidative stress through induction of PPAR-γ in VSMCs, which is accompanied by suppression of VSMC proliferation. In keeping with this, nicotinate-curcumin, an esterification derivative of niacin and curcumin, markedly prevents Ang IIinduced VSMC phenotype switching, proliferation, and migration via regulating the PTEN/AKT pathway (Sun et al, 2021). As a group of short non-coding RNA, micro RNAs (miRNA) plays a critical role in the process of human diseases, including hypertension (Zhang and Sun, 2020;Zhang and Sun, 2021).…”
Section: Inhibition Of Vascular Smooth Muscle Cell Proliferation and ...mentioning
confidence: 93%
“…Indeed, a study by Li et al (2017) has shown that curcumin attenuates Ang II-induced expressions of inflammatory factors and oxidative stress through induction of PPAR-γ in VSMCs, which is accompanied by suppression of VSMC proliferation. In keeping with this, nicotinate-curcumin, an esterification derivative of niacin and curcumin, markedly prevents Ang IIinduced VSMC phenotype switching, proliferation, and migration via regulating the PTEN/AKT pathway (Sun et al, 2021). As a group of short non-coding RNA, micro RNAs (miRNA) plays a critical role in the process of human diseases, including hypertension (Zhang and Sun, 2020;Zhang and Sun, 2021).…”
Section: Inhibition Of Vascular Smooth Muscle Cell Proliferation and ...mentioning
confidence: 93%
“…Sun et al found that Nicotiniccurcumin(1 μM) and curcumin(10 μM) could inhibit Ang II-induced VSMCs switching from a contractile to a synthetic phenotype by regulating the phosphatase and tensin homolog(PTEN)/Akt pathway. 85 (Figure 4 and Table 1)…”
Section: Protection Of Vsmcs By Curcuminmentioning
confidence: 99%
“…PTEN depletion promotes enhanced Phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/ mammalian target of rapamycin (mTOR) signaling under basal conditions and induces VSMC phenotypic modulation (Furgeson et al 2010). Nicotinate-curcumin inhibits AngII-induced VSMC phenotype switching via upregulation of PTEN expression and blocking the activation of phosphorylated AKT (Sun et al 2021). Besides, decreased (Cherepanova et al 2016;Salmon et al 2012;Yu et al 2011).…”
Section: The Transcription Factors Related To the Phenotypic Switchmentioning
confidence: 99%